Why do Third Sector Employees Intend to Remain or Leave their Workplace? - Selander, Kirsikka; Ruuskanen, Petri (Nordic Journal of Working Life Studies, 2016)
Third sector employees have claimed to enjoy high job satisfaction and low turnover intentions because their work is considered intrinsically rewarding. Employees have strong motivation for public service and they consider the organization’s goals as their own. This makes work meaningful and thus reduces turnover intentions. Changes in the third sector institutional environment, however, have intensified the working environment. This probably undermines job quality and thus increases turnover intentions. The analysis conducted among Finnish third sector employees showed that third sector employees report more turnover intentions than their counterparts in the public or private sector. This is mostly because of low job quality. Motivation for public service was not enough to retain employees in the organization if their values were not congruent with those of the employer organization. Thus, connection between public service motivation and turnover intentions is dependent on the organizational context. More important than employees’ desire to help others is their sharing of the employer organization’s values and that the organization provides high job quality.